A Case of Congenital Nephrogenic Diabetes Insipidus Caused by Thr108Met Variant of Aquaporin 2 - Ma, Lina; Wu, Dengyan; Wang, Xingmin; Yang, Yonghong (Frontiers in Pediatrics, 2020)
Congenital nephrogenic diabetes insipidus (CNDI) is a rare renal disorder caused by mutations in arginine vasopressin receptor 2 (AVPR2) or aquaporin 2 (AQP2). The clinical signs of CNDI include polyuria, compensatory polydipsia, dehydration, electrolyte disorder, and developmental retardation without prompt treatment. In this study we report a rare case of CNDI caused by a single base transition in AQP2 gene. A 4.5 years old male patient suffered from oral dryness, polydipsia, and polyuria for more than 3 years. Laboratory examinations showed hypernatremia, hyperchloremia, and decreased urine osmolality and specific gravity. Ultrasound and MRI found bilateral upper ureteral dilatation and hydronephrosis. Furthermore, sequencing analysis found a C>T transition leading to a T108M missense mutation of AQP2. The patient was given low sodium diet and treated with hydrochlorothiazide followed by amiloride with indomethacin. The patient’s clinical course improved remarkably after one year of treatment. This study reports the first case of CNDI featuring T108M missense mutation alone. These findings demonstrate a causative role of T108M mutation for CNDI and contribute to the mechanistic understanding of CNDI disease process.